Investigating the Effect of Ear Canal Length on Improving Earplugs and Earmuffs Performance at 400 and 500 Hz Frequencies - Hossein Ebrahimi; Farhad Forouharmajd; Siamak Pourabdian; Kamyar Nazaryan (International Journal of Environmental Health Engineering)
Aim: The aim of this study was noise reduction at 400 Hz and 500 Hz frequencies using earplugs and earmuffs, by varying the length of a simulated ear canal. Methods: This descriptive, analytical, and cross-sectional study was conducted in a laboratory environment using a simulated human hearing system based on the anatomical characteristics of the ear. Two types of earplugs and two types of earmuffs were tested. Using LABVIEW software, sound at 400 Hz and 500 Hz frequencies was generated by an ev-av150e sound generator at an 80 dB sound pressure level (weight A) with pink noise through a desktop speaker. A measurement microphone (1/2”, B and K brand) placed at the end of the ear canal, acting as the tympanic membrane, transmitted the received waves to a Data AcQuisition (DAQ) processing center system. Measurements were conducted for ear canal lengths of 20, 25, and 35 mm to assess the noise reduction capabilities of the hearing protection devices at these lengths. The data, reflecting sound attenuation across different lengths and devices, were evaluated and analyzed using SPSS version 26 for comparison under variable conditions. Results: There was a significant relationship between changes in the length of the external ear canal and the amount of noise reduction at 400 Hz and 500 Hz frequencies when using earplugs and earmuffs (P < 0.05). Conclusion: The results indicated that the performance of earplugs and earmuffs differed at these frequencies. Specifically, the effectiveness of earplugs increased with longer ear canal lengths, whereas the effectiveness of earmuffs decreased with longer ear canal lengths.